Role of shear stress in nitric oxide-dependent modulation of renal angiotensin II vasoconstriction - Endlich, Karlhans (British journal of pharmacology, 1999)
Renal vasoconstriction in response to angiotensin II (ANGII) is known to be modulated by nitric oxide (NO). Since shear stress stimulates the release of a variety of vasoactive compounds from endothelial cells, we studied the impact of shear stress on the haemodynamic effect of ANGII in isolated perfused kidneys of rats under control conditions and during NO synthase inhibition with L-NAME (100 μM).Kidneys were perfused in the presence of cyclo-oxygenase inhibitor (10 μM indomethacin) with Tyrode's solution of relative viscosity ζ=1 (low viscosity perfusate, LVP) or, in order to augment shear stress, with Tyrode's solution containing 7% Ficoll 70 of relative viscosity ζ=2 (high viscosity perfusate, HVP).Vascular conductance was 3.5±0.4 fold larger in HVP as compared with LVP kidneys, associated with an augmentation of overall wall shear stress by 37±5%. During NO inhibition, vascular conductance was only 2.5±0.2 fold elevated in HVP vs LVP kidneys, demonstrating shear stress-induced vasodilatation by NO and non-NO/non-prostanoid compound(s).ANGII (10-100 pM) constricted the vasculature in LVP kidneys, but was without effect in HVP kidneys. During NO inhibition, in contrast, ANGII vasoconstriction was potentiated in HVP as compared with LVP kidneys.The potentiation of ANGII vasoconstriction during NO inhibition has been shown to be mediated by endothelium-derived P450 metabolites and to be sensitive to AT2 receptor blockade in our earlier studies. Accordingly, in HVP kidneys, increasing concentrations of the AT2 receptor antagonist PD123319 (5 and 500 nM) gradually abolished the potentiation of ANGII vasoconstriction during NO inhibition, but did not affect vasoconstriction in response to ANGII in LVP kidneys.Our results demonstrate, that augmentation of shear stress by increasing perfusate viscosity induces vasodilatation in the rat kidney, which is partially mediated by NO. Elevated levels of shear stress attenuate renal ANGII vasoconstriction through enhanced NO production and are required for AT2 sensitive potentiation during NO inhibition.